Meaningful Public Participation in Environmental Decision-Making Process: A Comparative Study on EIA Preparation in Indonesia and the United States - Bimo Fajar Hantoro; Abdul Aziz Nasihuddin; Manunggal Kusuma Wardaya; Hermawan Prasojo; Syarafina Dyah Amalia (Program Pascasarjana Fakultas Hukum Universitas Sebelas Maret Surakarta, 2026)
Meaningful public participation has become an essential tool for ensuring accountability and empowering the public in environmental decision making. However, in Indonesia, public participation in EIA (Environmental Impact Assessment) preparation has suffered a regression post-Job Creation Law. This research is meant to analyze public participation in EIA preparation through a comparative perspective between Indonesia and the United States, followed by reform proposals drawn from the comparative study. This research is normative, employing statutory, conceptual, and comparative approaches. The findings show that the current EIA preparation process post-Job Creation Law has diminished the role of public participation evident in the screening process, the restrictions on the stakeholders involved and the comments considered, and the replacement of the EIA Review Commission with the less representative Environmental Feasibility Assessment Team (EFAT). In comparison, the United States NEPA (the National Environmental Policy Act) and its implementing regulations require public participation from the outset of the process and require responsible agencies to respond adequately to submitted comments, subjecting them to judicial review for failure to involve the public and respond to public comments. Based on NEPA practices, reforms to Indonesia's current EIA preparation includes replacing the screening process with EA (Environmental Assessment) for more contextual determination of significant impacts, involving environmental groups and indirectly affected communities at every stage of the EIA preparation, requiring the project initiators to adequately respond to comments and to publish a ROD (Record of Decision), and allowing judicial oversight through civil and public interest causes of action to ensure accountability.